Children and the Law. Profiles of Promise 15 - Pratt, Francis; Haley, Frances; Social Science Education Consortium, Inc., Boulder, CO.; ERIC Clearinghouse for Social Studies/Social Science Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The Greenwood School near Minneapolis adapted to their community the Children and the Law program, developed for fifth graders under the auspices of the Minnesota State Bar Association. The program seeks to remove the uncertainty children have about law and make them aware of its function, protecting individual and public rights; provides workshops for teachers and community participants; and emphasizes direct contact between students and policemen, lawyers, and judges. Curriculum materials are flexibly arranged for any classroom application and center on an activity booklet, A Look at Law, which provides familiar situations for student discussion, simulation, and role playing. A television series, Children and the Law, developed by KTCA-St. Paul is also used with the program. Special activities at Greenwood School include use of other films on law related topics such as shoplifting and highway safety; a visit from the country sheriff's mobile crime laboratory; and student presentations to the Village Council requesting the construction of an outdoor swimming pool. Reaction to the program from students and parents has been enthusiastic. (Author/JH)
Availability: Social Science Education Consortium, 855 Broadway, Boulder, Colorado 80302 ($9.00 for 30 issues).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
ERIC Note: For a description of the Profiles of Promise series, see ED 090 080; SO 007 163 is a related document.
Educational level discussed: Elementary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Instruction; Citizenship; Community Involvement; Community Resources; Delinquency Prevention; Educational Innovation; Elementary Education; Instructional Programs; Learning Activities; Legal Education; Relevance (Education); School Community Relationship; Teacher Workshops; Profiles of Promise; Journal Articles